Talent Development in Basketball: A Perspective from Brazilian Coaches - Dilson Borges Ribeiro Junior; Jeferson Macedo Vianna; Hélder Zimmermann de Oliveira; Emerson Filipino Coelho; Antonio Antúnez; Francisco Zacaron Werneck, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The coach plays a central role in the identification, selection, and development of talent. The aim of this study was to investigate into the opinions of Brazilian coaches about the importance of different factors for the development of young basketball players. A total of 94 coaches from different clubs and with diverse professional experience are administered a questionnaire on anthropometric, physical, technical, tactical, psychological, and environmental characteristics. On a scale of 1 (not at all important) to 5 (extremely important), the coaches indicated to what extent a factor/indicator of athletic potential was important for the development of a young basketball player. Repeated measures ANOVA showed that, in the coaches' opinion, the technical and physical factors were the most important in relation to the other factors for the development of young basketball players, with differences according to the playing position. Most coaches considered the following indicators of the sporting potential as extremely important: Shooting skill, passing and individual defense technique, speed, agility, and lower limb strength. The coaches also considered tactical skills, especially positioning and decision-making, as well as the quality of practice and psychological skills (confidence, withstanding pressure, concentration, dealing with adversity, coachability, and determination) to be extremely important. The relevance of these indicators varied according to the competitive level of the coaches (international vs. regional/national). Our results can potentially help coaches in the process of identifying and developing talents for the Brazilian basketball.